Postharvest UV-C Treatment Affects Bioactive Compounds and Maintains Quality of Okra (Abelmoschus esculentus L.) during Storage - Chairat Techavuthiporn; Amnat Jarerat; Chonlada Singhkai; Hataitip Nimitkeatkai (The Horticulture Journal, 2023)
The effects of UV-C treatment on physicochemical quality, bioactive compounds and antioxidant activity of okra (Abelmoschus esculentus L.) during storage were investigated. Okra pods were exposed to UV-C irradiation dose at 1.5, 3.0 or 6.0 kJ·m−2 before storage at 10 ± 2°C for 12 days. The results showed that UV-C treatment had a significant effect on okra bioactive compounds, such as ascorbic acid, total phenolic, flavonoid contents and antioxidant activity. The highest values of these compounds were observed in okra treated with 6.0 kJ·m−2 UV-C irradiation. A statistical analysis of the data demonstrated that mucilage had a favorable association with antioxidant capabilities and bioactive substances in response to UV-C treatment. Moreover, UV-C treatment also effectively maintained the quality of okra during storage, as evidenced by lower weight loss and higher firmness without incidence of decay. Therefore, postharvest UV-C treatment can be a potential approach to enhance bioactive compounds and maintain the quality of okra during storage.
Keywords: Postharvest Quality and Shelf Life Management; Agricultural Practices and Plant Genetics; Essential Oils and Antimicrobial Activity